Changing trends of blood transfusion requirement in obstetrics and gynaecology - Singh, Rajesh Kumar; Anne, Sirisha; P., Sruthi Ravindran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: With the advent of the new pharmacological drugs and surgical advances compared to yesteryears, that the requirement of blood transfusion in obstetrics and gynaecology has decreased. Earlier obstetrical haemorrhage had been the commonest reason for blood transfusion. This trend seems to be changing. To evaluate this an observational study was done at a peripheral hospital to assess various indications for blood transfusion in maternity ward over a period of one year. Methods: A total of 129 transfusions were studied in a period of one year and requirement of transfusion was assessed by the same team of doctors as per AABB guidelines for blood transfusion. Results: A total of 87 obstetric patients required transfusion out of which 51.2% patients were transfused for anaemia near term. Postpartum haemorrhage constituted only 1.15% and ante partum haemorrhage only 4.6%. 17.24% of patients were transfused for incomplete abortion after taking medical abortion. 42 patients were transfused blood for various gynaecological reasons of which puberty menorrhagia constituted 19.01% and patients with perimenopausal bleeding were 28.57%. Conclusions: This study highlights the changing trends in requirement of blood transfusion and the need to emphasise on antenatal nutrition, supplements and contraception.